PETA KEKUTAN EKONOMI SYARIAH DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN (MEA) - Itang, Itang (ALQALAM, 2015)
This paper examines the economic power of sharia that is not only able to survive but also can grow in the free market zone in Southeast Asia (ASEAN Economic Community (AEC)). The Islamic economic strength in Indonesia can be based on several reasons namely: 1). Muslim population. As the country with the largest Muslim population of about (87-90%), Indonesia should be the pioneer and the great power of Islamic finance in the world 2). Inherent Islamic doctrine and human resources. 3). Regulation of Islamic Economics as a tool that can legalize all policies the implementation of Islamic Economics. 4). Actors of Islamic Economics that come from various backgrounds such as practitioners, academics and customers. 5). Islamic Financial Industry Development. According to the data from Bank Indonesia in October 2013, there are 11 Islamic Banks, 23 Islamic Banks in the form of Sharia Business Unit , and 160 small sharia banks that distribute the fund for the people. Islamic banking assets currently has reached Rp. 228 trillions. The development of Islamic financial institutions does not only reach Islamic banks but also Islamic non banks such as insurance and pawnshop. Therefore we  are optimistic that sharia economy can grow in ASEAN Economic Community (AEC).Key word: sharia economy , islamic finance, AEC , ASEAN ,